Total Flavones of Rhododendron Protect Against Ischemic Cerebral Injury by Regulating the Phosphorylation of the RhoA-ROCK2 Pathway via Endothelial-Derived H2S - Xiaoqing Sun; Xingyu Zhang; Yuwen Li; Jiyue Wen; Zhiwu Chen; Shuo Chen (Current Issues in Molecular Biology)
This study aims to investigate the mechanism by which the total flavones of Rhododendron (TFR) protect against cerebral ischemic injury through the endothelial-derived H2S-mediated regulation of RhoA phosphorylation at the Ser188 and Rho kinase 2 (ROCK2) phosphorylation at Thr436. For experimental design, mouse or rat cerebrovascular endothelial cells (ECs) were cultured with or without neurons and subjected to hypoxia/reoxygenation (H/R) injury. The vasodilation of the cerebral basilar artery was assessed. Cerebral ischemia/reperfusion (I/R) injury was induced in mice by bilateral carotid artery ligation, followed by Morris water maze and open field behavioral assessments. The protein levels of cystathionine-γ-lyase (CSE), 3-mercaptopyruvate sulfurtransferase (3-MST), RhoA, ROCK2, p-RhoA (RhoA phosphorylated at Ser188), and p-ROCK2 (ROCK2 phosphorylated at Thr436) were quantified. Additionally, the activities of RhoA and ROCK2 were measured. Notably, TFR significantly inhibited H/R-induced H2S reduction and suppressed the increased expression and activity of RhoA and ROCK2 in ECs, effects attenuated by CSE or 3-MST knockout. Moreover, TFR-mediated cerebrovascular dilation was reduced by RhoA or ROCK2 inhibitors, while the protective effect of TFR against cerebral I/R injury in mice was markedly attenuated by the heterozygous knockout of ROCK2. In the ECs-co-cultured neurons, the inhibition of TFR on H/R-induced neuronal injury and decrease in H2S level in the co-culture was attenuated by the knockout of CSE or 3-MST in the ECs. TFR notably inhibited the H/R-induced upregulation of neuronal RhoA, ROCK2, and p-ROCK2 protein levels, as well as the activities of RhoA and ROCK2, while reversing the decrease in p-RhoA. However, the knockout of CSE or 3-MST in the ECs significantly attenuated the inhibition of TFR on these increases. Furthermore, 3-MST knockout in ECs attenuated the TFR-mediated suppression of p-RhoA reduction. Additionally, CSE or 3-MST knockout in ECs exacerbated H/R-induced neuronal injury, reduced H2S level in the co-culture system, and increased RhoA activity and ROCK2 expression in neurons. In summary, TFR protected against ischemic cerebral injury by endothelial-derived H2S promoting the phosphorylation of RhoA at Ser188 but inhibited the phosphorylation of ROCK2 at Thr436 to inhibit the RhoA-ROCK2 pathway in neurons.